Biliary cystadenoma associated with Opisthorchis viverrini infection in a domestic cat (Felis catus) - Tiwananthagorn, Saruda; Srivorakul, Saralee; Khochakul, Varangpicha; Pringproa, Kidsadagon (Veterinary parasitology, 2018)
•This report described an unusual case of Opisthorchis viverrini infection associated with biliary tumor in a cat.•Pathological evaluation and molecular identification, a diagnosis of biliary cystadenoma associated with Opisthorchis viverrini infection was made in the cat.•The report raises attention to the role of the domestic cat as a reservoir host of the human liver fluke. A 12-year-old, female, domestic cat (Felis catus) presented with dehydration, emaciation, anorexia, and lethargy. The cat was unresponsive to medical treatment and euthanized; the carcass was submitted for pathological diagnosis. Necropsy revealed icteric mucous membranes. The liver was enlarged, with multinodular, cystic, white masses, 0.5–4.0 cm in diameter, scattered throughout. Microscopically, the biliary epithelium presented with a proliferation of multifocal cystic masses, occasionally with periodic acid–Schiff-positive fluid within the cysts. Simple cuboidal epithelial cells showed small, round to oval, vesicular nuclei and rare mitotic figures. There were also multifocal trematode-like parasites situated within the biliary tracts. Immunohistochemistry of the cystic masses was positive for pan-cytokeratin and proliferating cell nuclear antigen, while negative for vimentin. Molecular analysis and gene sequencing of the parasite indicated that it was Opisthorchis viverrini. Based on the pathological findings and molecular analysis, the cat was diagnosed with biliary cystadenoma related to O. viverrini infection. This report described an unusual case of O. viverrini infection associated with biliary tumor in a cat, and raises the possibility of domestic cats as a reservoir host of the human liver fluke.